2015
DOI: 10.11607/ijp.4119
|View full text |Cite
|
Sign up to set email alerts
|

Retrievability of Implant-Supported Crowns When Using Three Different Cements: A Controlled Clinical Trial

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 0 publications
3
24
0
2
Order By: Relevance
“…[25][26][27] Previous studies have evaluated the pullout retention values for metal abutments with different cements and demonstrated that the cement type influences the retentiveness level of the prosthesis. 27,28 Additionally, some authors suggested that provisional cements could be adequate for conventional cement-retained, implantsupported crowns, 29,30 which is supported by our findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[25][26][27] Previous studies have evaluated the pullout retention values for metal abutments with different cements and demonstrated that the cement type influences the retentiveness level of the prosthesis. 27,28 Additionally, some authors suggested that provisional cements could be adequate for conventional cement-retained, implantsupported crowns, 29,30 which is supported by our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have evaluated the pullout retention values for metal abutments with different cements and demonstrated that the cement type influences the retentiveness level of the prosthesis . Additionally, some authors suggested that provisional cements could be adequate for conventional cement‐retained, implant‐supported crowns, which is supported by our findings. The results of the current study demonstrated that resin‐based cement presented significantly higher pullout strength compared to the provisional cement group, and also compared to groups without cement (data collapsed over crown material).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride is a corrosive agent known to affect titanium and its alloys, with hydrofluoride etchant commonly used to clean and etch titanium. 17 Both of these polycarboxylate cements have been reported to increase restoration retention when used with titanium abutments, [9][10][11][12] caused perhaps by a chemical interaction. 10,11 However, aside from speculation, this has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported unexpectedly high bonding values of polycarboxylate cements with titanium structures, leading the authors to speculate that a bonding mechanism to titanium exists. [9][10][11][12] Several reports indicate that some dental cements alter the protective titanium oxide layer, resulting in color changes to the titanium surface. 12,13 The instructions for use with one polycarboxylate cement (Durelon; 3M ESPE) state that "a discoloration effect may result when used with titanium."…”
mentioning
confidence: 99%
See 1 more Smart Citation